Seashore - Parker, Steve; King, Dave. (London Dorling Kindersley, 1989)
Brief text and photos introduce the animal inhabitants of the seashore, including fish, crustaceans, snails, and shorebirds.
"DK Eyewitness books"--at head of title.
Keywords: Seashore biology -- Juvenile literature; Seashore biology